PENGARUH PERECANAAN DAN PELAKSANAAN ANGGARAN TERHADAP PENYERAPAN ANGGARAN (STUDI KASUS PADA KECAMATAN BACAN, KECAMATAN BACAN SELATAN DAN KECAMATAN BACAN TIMUR) - Husen, M Aprialdy; Bailusy, Muhsin N; Hadady, Hartaty (Jurnal Manajemen Sinergi, 2022)
The main objectives of this study were to determine andanalyze: the influence of planning on budget absorption in Bacan subdistrict,southern Bacan sub-district and eastern Bacan sub-district; andthe influence of the budget on budget absorption in Bacan sub-district,southern Bacan sub-district and eastern Bacan sub-district.Methodology: This study uses multiple linear regression analysis usingSPSS version 23 as a statistical test tool. The data collection tools usedwere questionnaires and interviews, and the number of respondentswas 99 respondents spread over the southern Halmahera district.Finding: In the regression output, the significance number for thePlanning variable is 0.731. This value is greater than the significancelevel of 0.05 so that it states that budget planning has no effect onbudget absorption and it can be concluded that H1 is rejected becauseit is supported by the data and is not in accordance with researchexpectations. At the output of the regression obtained a significantfigure for the budget implementation variable of 0.000. This value issmaller than the significance level of 0.05, indicating that budgetexecution has a positive effect on budget absorption and it can beconcluded that H2 is accepted.Conclusion: (1) Planning has no effect on budget absorption in BacanDistrict, South Bacan District and East Bacan District. It can be seenfrom the significance figure for the budget planning variable that it is0.731 because there are still many village officials who have planned orhave budgeted for a plan but in implementation it is not realized so thatit can weaken the absorption capacity of the budget; and (2) budgetimplementation has an effect on budget absorption in South Halmaherain Bacan District, South Bacan District and East Bacan District. It canbe seen from the significance figure for the budget implementationvariable, which is 0.000. Because if the implementation is good, it canabsorb the budget itself and vice versa.